Income and Beyond : Multidimensional Poverty in Six Latin American Countries - Battiston, Diego; Cruces, Guillermo; López-Calva, Luis F.; Lugo, Maria Ana; Santos, Maria Emma (Springer Netherlands, 2016)
This paper studies multidimensional poverty for Argentina, Brazil, Chile, El Salvador, Mexico and Uruguay for the period 1992–2006. The approach overcomes the limitations of the two traditional methods of poverty analysis in Latin America (income-based and unmet basic needs) by combining income with five other dimensions: school attendance for children, education of the household head, sanitation, water and shelter. The results allow a fuller understanding of the evolution of poverty in the selected countries. Over the study period, El Salvador, Brazil, Mexico and Chile experienced significant reductions in multidimensional poverty. In contrast, in urban Uruguay there was a small reduction in multidimensional poverty, while in urban Argentina the estimates did not change significantly. El Salvador, Brazil and Mexico, and rural areas of Chile display significantly higher and more simultaneous deprivations than urban areas of Argentina, Chile and Uruguay. In all countries, deprivation in access to proper sanitation and education of the household head are the highest contributors to overall multidimensional poverty.